Andrew Sobanet. Generation Stalin: French Writers, the Fatherland, and the Cult of Personality. Indiana UP, 2018. - E. Nicole Meyer (Studies in 20th & 21st Century Literature, 2020)
Review of Andrew Sobanet. Generation Stalin: French Writers, the Fatherland, and the Cult of Personality. Indiana UP, 2018. xi + 296 pp.
Keywords: Sobanet; Stalin; Barbusse; Aragon; Eluard; Rolland